Anecdotal Text Theme ‘Gulai Nangka’ According to Student Choice Using Google Classroom Media - Rasdana, Oki; Akhmad, Imam (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe: 1) the central theme of the anecdote text ‘Gulai Nangka’ according to students’ choices using google classroom media; 2) supporting theme-1 of the anecdote text ‘Tangga Sakti’ according to students’ choices using google classroom media; 3) supporting theme-2 of the anecdote text ‘Tangga Sakti’ according to students’ choices using google classroom media. The study was conducted in the odd semester of 2024/2025 at the Indonesian Language and Literature Education Study Program, University of Riau. The population consisted of students in the 3rd semester of the 2024/2025 academic year who submitted the Google form. There were 88 students divided into three parallel classes. The sample was determined to be 73 students based on the Slavin formula. This number is divided into 25 students in class 2023A and 25 students in class 2023C. Data on the theme of the anecdote text ‘Gulai Nangka’ according to students’ choices were collected using a closed questionnaire in the electronic version of the Google using google classroom media. This questionnaire is valid because it is compiled using objective and systematic procedures. The data on the main themes of the anecdote text ‘Gulai Nangka’ according to students’ choices were analyzed using descriptive statistical procedures that focused on frequency, percentage, and mode. The results of the study: 1) the central theme of the anecdote text ‘Gulai Nangka’ according to students’ choices is that people always choose the best; 2) the supporting theme-1 of the anecdote text ‘Gulai Nangka’ according to students’ choices is that a good way of processing determines the deliciousness of a dish; 3) the supporting theme-2 of the anecdote text ‘Gulai Nangka’ according to students’ choices is the shifting of focus from good things to bad things.